Legal education on the protection of women and children from violence in Mantowu Village, Buton - Samsul Samsul; La Gurusi; Eko Satria; Waode Novita Ayu Muthmainna; La Asiri; Muh. Rahmatul; Sapril Sapril (Community Empowerment, 2024)
Cases of violence against women and children in Buton Regency often go unreported, resulting in an increasing number of cases each year. Several contributing factors include the lack of community participation in providing information and support to victims, as well as a tendency to blame the victims. This condition discourages victims from fighting for their rights. To address this issue, legal education on the protection of women and children at the village level is essential. The objective of this activity is to enhance community understanding and participation in making Buton Regency free from violence against women and children. The method used in this Community Service activity is legal counseling. Prior to the counseling, the initial step involved identifying and inventorying the problems faced by the community. After conducting legal education through counseling sessions, the community demonstrated an increased understanding of the importance of protecting women and children, as well as their role in preventing violence and providing support to victims. This education is expected to contribute to creating a safer and more supportive environment for women and children in Buton Regency.